An agro-economic survey of the weeds and weeding practices in cassava (Manihot esculenta Crantz) in Colombia - Doll, J.; Pinstrup-Andersen, Per; Díaz, R.O. (Wiley, 1977)
A survey of weeds and weeding practices was carried out by a team of agricultural economists and agronomists on 283 farms in 5 cassava-growing regions of Colombia at 3 times during a cropping season. From 71-78 percent of the weed species present were broad- leaved species. As cassava grew older, grass species were present to a greater extent and sedge species to a lesser relative frequency. Surprisingly, Pteridium aquilinum was the most frequently listed species, in addition to Bidens pilosa and Cyperus rotundus. Regional variations in the most frequently encountered species were found, but several of the weeds were common to many zones. The most frequently encountered species did not usually have the highest plant populations. Most of the annual grasses, sedges and broad-leaved weeds found can be controlled by currently recommended herbicides for cassava, but further research is needed on Imperata cylindrica, Melinis minutiflora, P. aquilinum and Sida spp. The av no. of manual weedings was 3.3/crop, occupying 48 man-days/ha, which represents 50 percent of the total labor requirements for cassava production and more than 1/3 of the totalcosts. Reasons for not using herbicides were (1) relative costs of herbicides and labor, (2) lack of information, (3) lack of capital, (4) right herbicides were not available in small packages. This survey has identified new field problems and has suggested further research programs to solve them. (AS)